2014
DOI: 10.1111/edt.12120
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of maxillary Lefort Ι fracture with bioabsorbable osteosynthesis internal fixation

Abstract: The aim of this study was to apply biomechanical analysis model to evaluate the effects of bioabsorbable internal fixation devices on maxillary Lefort Ι fracture. CT scan technology and the finite element software (ansys) were used to establish three-dimensional finite element models of five resorbable internal fixation devices in maxillary Lefort Ι fractures. We used the model to calculate the stress of the upper jaw and internal fixation. We further analyzed the stability of fixation under four occlusions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Several studies assessed the mechanical forces surrounding osteosyntheses applied to maxillofacial fractures [ 157 , 158 , 159 , 160 , 161 , 162 , 163 ], osteotomies [ 164 , 165 ] and reconstructions [ 166 ], so that the minimally required mechanical properties of an osteosynthesis system can be estimated. After maxillofacial trauma, the reported bite force increases up to 64 N by the second postoperative fracture fixation day, 92 N after 1 week, 187 N after 4 weeks, and up to 373 N at the 3-month follow-up [ 157 ].…”
Section: Pre-clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies assessed the mechanical forces surrounding osteosyntheses applied to maxillofacial fractures [ 157 , 158 , 159 , 160 , 161 , 162 , 163 ], osteotomies [ 164 , 165 ] and reconstructions [ 166 ], so that the minimally required mechanical properties of an osteosynthesis system can be estimated. After maxillofacial trauma, the reported bite force increases up to 64 N by the second postoperative fracture fixation day, 92 N after 1 week, 187 N after 4 weeks, and up to 373 N at the 3-month follow-up [ 157 ].…”
Section: Pre-clinical Evidencementioning
confidence: 99%
“…Within the limitations of finite element analyses (e.g., assuming the masticatory forces are fixed), three-dimensional analyses indicated that the biomechanical stresses surrounding osteosynthesis systems remain far below the threshold of their ultimate strength of both biodegradable and titanium osteosynthesis systems [ 163 , 172 , 182 , 183 ]. In addition, the empirical evidence of fracture [ 19 ] and osteotomy [ 184 ] osteosyntheses shows that the efficacy of titanium and biodegradable osteosyntheses is similar (e.g., absence of malunion), indicating that the less favorable mechanical properties of biodegradable osteosynthesis are still sufficient to achieve similar healing outcomes.…”
Section: Pre-clinical Evidencementioning
confidence: 99%
“…Several studies assessed the mechanical forces surrounding osteosyn-theses applied to maxillofacial fractures [146][147][148][149][150][151][152] , osteotomies 153,154 and reconstructions 155 . After maxillofacial trauma, the reported bite force increases up to 64 N by the second postoperative fracture follow-up 146 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…surrounding (biodegradable) osteosynthesis systems remain far below the threshold of their ultimate strength 14,34,152,159 . In addition, the systematic reviews of fracture and osteosyntheses is similar (e.g., absence of malunion) indicating that the less favourable similar healing outcomes (Chapters 2 and 3).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation